Identification and Characterization of Switchgrass Histone H3 and CENH3 Genes - Miao, Jiamin; Frazier, Taylor; Huang, Linkai; Zhang, Xinquan; Zhao, Bingyu (Frontiers in Plant Science, 2016)
Switchgrass is one of the most promising energy crops and only recently has been employed for biofuel production. The draft genome of switchgrass was recently released; however, relatively few switchgrass genes have been functionally characterized. CENH3, the major histone protein found in centromeres, along with canonical H3 and other histones, plays an important role in maintaining genome stability and integrity. Despite their importance, the histone H3 genes of switchgrass have remained largely uninvestigated. In this study, we identified 17 putative switchgrass histone H3 genes in silico. Of these genes, 15 showed strong homology to histone H3 genes including six H3.1 genes, three H3.3 genes, four H3.3-like genes and two H3.1-like genes. The remaining two genes were found to be homologous to CENH3. RNA-seq data derived from lowland cultivar Alamo and upland cultivar Dacotah allowed us to identify SNPs in the histone H3 genes and compare their differential gene expression. Interestingly, we also found that overexpression of switchgrass histone H3 and CENH3 genes in N. benthamiana could trigger cell death of the transformed plant cells. Localization and deletion analyses of the histone H3 and CENH3 genes revealed that nuclear localization of the N-terminal tail is essential and sufficient for triggering the cell death phenotype. Our results deliver insight into the mechanisms underlying the histone-triggered cell death phenotype and provide a foundation for further studying the variations of the histone H3 and CENH3 genes in switchgrass.